Abstract: the artistic interpretation of abstract artworks / Clement Jimel - Jimel, Clement (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
This kind of work is a non-figurative interpretation of emotions, perceptions, and the human experience, which provides an insight into the individual-self. Their techniques make the viewers approach the art and imposes some topics on them, however, the topics require deeper appreciation. Sebastian Jong provides an example of The Natural Beauty of Sarawak, which applies acrylic pouring to represent the movement and the structure of nature. Such designs are supposed to give an impression of the area’s geography by depicting moving forms and colours, which makes the actual view portrayed by such patterns rather conjectural.